The Use of Interactive Multimedia to Address the Limitations of Conventional Methods in Islamic Religious Education - Nasywa, Dzihni Ashiilah; Cahyani, Ainun; Mutmainnah, Nisa; Qafilah, Kalvin Al; Azis, Abdul (El-Rusyd, 2026)
The teaching of Islamic Religious Education in various educational institutions still faces the challenge of a dominance of conventional methods, which tend to make students passive and less engaged in the learning process. This situation is exacerbated by the abstract nature of some Islamic Religious Education material, which makes it difficult to understand without the support of engaging media. This study aims to analyze the use of interactive multimedia in addressing the issues associated with conventional methods in Islamic Religious Education and to explore its role in supporting more active and innovative learning. The method used is qualitative research employing a content analysis approach to relevant literature. The findings indicate that interactive multimedia can enhance learning motivation, strengthen conceptual understanding, encourage active participation, and develop students’ digital literacy. Its application is relevant across various fields of Islamic Religious Education, though its success depends on educators’ competencies, the availability of facilities, and the appropriateness of instructional design. This study concludes that interactive multimedia is a potential innovative alternative for improving the quality of Islamic Religious Education in the digital age.